Isolated and combined effect of strength training and specific strength training on performance levels among archers - Chatla, A. K.; Narasimha Rao, K. V.; Pandey, D.; Devi, L. S.; Satyanarayana, V. (Teorija i metodika fizichnogo vihovannja, 2023)
Study purpose. The purpose of the study was to find out the impact of isolated and combined effect of Specific Strength Training, Strength Training, and Combined Strength Training on the performance levels among archers.